MARGINS WITHIN MARGINS: DUAL STRUGGLES OF HIJRA IDENTITY IN THE AUTOBIOGRAPHIES OF LAXMI AND REVATHI - Maibangsa, Hamsringdi; Jyoti Jayal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the dual struggles of hijra individuals in India and deals with the marginalization they experience both within mainstream society and within their community. Through a critical analysis of two autobiographies titled Me Hijra, Me Laxmi by Laxmi Narayan Tripathi and The Truth About Me: A Hijra Life Story by A. Revathi, this study investigates how language is used to construct, resist, and negotiate power. Norman Fairclough’s Critical Discourse Analysis (CDA) and Gayatri Chakravorty Spivak’s theory of subalternity have been employed in this study to explore how autobiographical narratives can be used to investigate the ideology and power structures that are involved in their dual marginalization.